The occurrence of Lactobacillus and Candida albicans in patients with thyroid disorders - Riam Hassoun Harbi1 - Maha Adel Mahmood2 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Thyroid disease can disrupt the body's balance and affect its ability to heal tissues. Research has indicated that those with thyroid problems have an increased susceptibility to dental caries. This may be from the illness process itself, surgical intervention (thyroidectomy), or drug side effects that exacerbate dental and oral health conditions. The case-control study was conducted 87 precipitate. Precipitate was divided into three groups as the following: hyperthyroidism, hypothyroidism, and healthy control group. Each group comprised 29 subjects, all participants aged between 30 and 60.  Saliva was cultured on orgasm agar for lactobacilli, sabouraud’s dextrose agar for Candida albicans. Additionally, thyroid function test was measurement by cobas. Concerning (salivary flow rate), results show that a lower mean value was recorded in the "Hyperthyroid" patient group, whereas in the "Hypothyroid" group, patients accounted for the second-ordered mean value, and the healthy group accounted for a high-level mean value within the normal range, as significant differences at P<0.05 were accounted for among the studied groups. Concerning microbial types, comparing hyperthyroid and control groups, results show that substantial differences are accounted for in at least P<0.05 (C. Albicans and Lactobacillus). Also, comparing hypothyroid and control groups shows significant differences, at least at P<0.05. This study concluded that salivary flow rate (SFR) is too sensitive due to hyperthyroid patients, and C. Albicanis and Lactobacillus) have a higher count in Saliva of both hyperthyroid and hypothyroid patients compared with the control group,